Analsis Kebijakan Dividen dan Kinerja Keuangan Terhadap Nilai Perusahan - asna, asna; Jehoni, Yeremia Naigo; Irma Tyasari (Fakultas Ekonomika dan Bisnis Universitas PGRI Kanjuruhan Malang, 2025)
Abstract The purpose of this study is to determine the effect of dividend policy, liquidity, leverage and profitability on company value in food and beverage companies listed on the Indonesia Stock Exchange simultaneously and partially. Research conducted based on quantitative methods. The determination of this research sample used the purposive sampling method so that research samples were obtained as many as 17 food and beverage companies listed on the Indonesia Stock Exchange. This research data uses the financial statements of manufacturing companies for the 2020-2022 period. The data analysis method used is multiple linear regression. The results proved that simultaneously dividend policy, liquidity, leverage and profitability had a significant effect on the value of the company. The partial results prove that dividend policy has a significant effect on the value of the company, liquidity has a significant effect on the value of the company, leverage has a significant effect on the value of the company and profitability has a significant effect on the value of the company. This result proves that good company value is supported by an increase in dividend policy value, liquidity, leverage and profitability. Keywords – Dividend Policy, Leverage, Liquidity, Profitability, Company Value